ナンキョク ショウワキチ ミズホキチ カン ノ VHF/HF ツウシン - 野崎, 憲朗; ノザキ, ケンロウ; Nozaki, Kenrou (1983)
P(論文) オーロラ発生時の電離層E層不規則構造によるVHF電波散乱通信実験が昭和基地, みずほ基地間で行われた。オーロラ散乱の特性上電波の伝搬通路は大圏コースから大きくはずれる。VHF電波散乱の時間発生率は5%程度で, 昭和基地でのオーロラレーダーのエコー発生, 地磁気じょう乱と良い相関がある。電離層じょう乱により障害を受けやすい両基地間の短波通信と地磁気じょう乱に対する特性を比較して, 短波通信とVHF通信の相補性について論じた。 Radio telecommunication characteristics between Syowa Station and Mizuho Station were studied by using VHF radio wave scattered by ionospheric E-layer irregularity accompanied with aurora. VHF radio wave was propagated in a path greatly different from the great circle course according to the irregularity structure. Total reception time rate was about 5% and VHF radio scatter had good correlation with radar aurora and geomagnetic irregularity at Syowa Station. Geomagnetic irregularity effect on VHF radio scatter was compared with that on HF telecommunication which is easily affected by ionospheric conditions. Complemental relations between HF and VHF telecommunications were discussed. departmental bulletin paper